The Validity of Submission in Credit Agreements Based on Sharia Principles - Prawatya Ido Nurhayati; Yeni Oktafia (Transpublika Publisher, 2025)
The purpose of the study is to investigate on the concept of submission in legs of credit agreements based on Shariah concept. This research is intended to measure the legality of these agreements based on the requirements of contract in accordance with the stipulation set out in Article 1320 of the Option of Contractual Law, so that only those agreements in respect of the law, so that all concerned parties must comply with the legal principles set forth by law. Moreover, this research also aims to evaluate and determine the authority of the Religious Court to resolve disputes arising from implementation of Shariah credit agreement entries. This study used a normative juridical research method to analyze the relationship between credit agreements and Shariah. The motivation for this study is the increasing number of Shariah credit agreements formed lately, some of which are not based on the basic principles of Shariah credit agreements. The results of the research show that the jurisdiction of Religious Courts to resolve these disputes is governed by Law Number 3 of 2006 concerning the Religious Courts, so that although there is wide jurisdiction for these courts in principle, there are still limitations in the authority of these courts to resolve disputes arising from the execution of the Shariah credit agreement.